Changes in Function After a 6-Month Walking Intervention in Patients With Intermittent Claudication Who Are Obese or Nonobese. Issue 4 (October 2017) - Addison, Odessa; Ryan, Alice S.; Prior, Steven J.; Katzel, Leslie I.; Kundi, Rishi; Lal, Brajesh K.; Gardner, Andrew W.
Abstract : Background and Purpose: Both obesity and peripheral artery disease (PAD) limit function and may work additively to reduce mobility. The purpose of this study was to compare the effects of a 6-month, center-based walking program on mobility function between adults who are weight-stable obese and nonobese with PAD. Methods: This is a secondary data analysis of 2 combined studies taken from previous work. Fifty-three adults with PAD and intermittent claudication participated in 6 months of treadmill training or standard of care. Patients were divided into 4 groups for analyses: exercise nonobese (Ex), exercise obese (ExO), standard-of-care nonobese (SC), and standard-of-care obese (SCO). Mobility was assessed by a standardized treadmill test to measure claudication onset time (COT) and peak walking time (PWT) as well as the distance walked during a 6-minute walk distance (6MWD) test. Results: There was a significant ( P < .001) interaction (intervention × obesity) effect on 6MWD, wherein both exercise groups improved (Ex = 7%, ExO = 16%; P < .02), the SC group did not change (0.9%; P > .05), and the SCO group tended to decline (−18%; P = .06). Both exercise intervention groups significantly improved COT (Ex = 92%, ExO = 102%; P < .01) and PWT (Ex = 54%, ExO = 103%; P < .001). There was no change ( P > .05) in either standard-of-care group. Conclusions: Individuals who are obese and nonobese with PAD made similar improvements after a 6-month, center-based walking program. However, patients who are obese with PAD and do not exercise may be susceptible to greater declines in mobility. Exercise may be particularly important in patients who are obese with PAD to avoid declines in mobility.